Neoliberalism and postmodernism: The sacylla and charybdis for critical pedagogy and what can be done about it - Letizia, Angelo (Journal of Interdisciplinary Studies in Education, 2015)
The rise of neoliberalism during the late 1970s in the West however fundamentally questioned the role of higher education institutions in the process of public good formation. Neoliberals and postmodernist generally chafe at what they consider improbable utopianism albeit for different reasons (Allan, 2011). Yet, there are many of us who hold to the ideals of critical pedagogy and believe that justice can be achieved through education. The purpose of this paper is to demonstrate ways in which higher education institutions and critical theorists can create knowledge which promotes the public good, in light of neoliberalism and the postmodern critique. Ultimately, I call for the creation of a new academic discipline, higher education and the public good.